Building iPhone OS Accessories - Maskrey, Ken (Apress, 2012)
With the announcement at WWDC 2009 of the EAAccessory Framework, I had two instant thoughts: (1) this is really cool and could make someone a lot of money, and (2) I’m probably already too late. This second thought was because, at the time, there were probably about 100,000 apps in the App Store and it had been around a year, I think. I thought there was no way I could develop all the cool accessories I had in my head before other people and companies had done it and it’d be just like the App Store. But I decided to try anyway, always keeping an ear out for what was going on in the accessory world. The obvious first project was a credit card reader for the iPhone. From my shop, Mac Medics, I repair anywhere from two to ten iPhone screens a day, six days a week. It makes me a nice little bit of green. What I learned was that at least three-quarters of my customers were business people who used their iPhones for business. Most of them really would have liked to have a way to accept credit cards on their iPhones. At the time, there were several apps that did just that, but no accessories. A software-only solution has two problems: it is manual entry so prone to mistakes, and processing a card this way results in higher merchant fees. A physical reader solves both problems. So off I went, still keeping an eye on what was happening in the market. Eventually, I turned out a nice product that, I feel, blew away any competition. What competition might you ask? Well, I won’t get specific, but if you do a little research you’ll see that, as I write this in April 2010, there’s really only a single product out there that’s been delivered. One other is expected to deliver shortly. Regardless of whose product is better, the moral of the story is: hey, there’s not a whole lot of stuff out there!